Implementasi bahan ajar fisika terintegrasi kecerdasan spiritual dalam model pembelajaran berbasis masalah pada kelas X SMAN 16 Padang - wita nirmala; zulhendri kamus; Yulkifli yulkifli; renol afrizon (PILLAR OF PHYSICS EDUCATION, 2019)
The purpose learning in 2013 curriculum is demanding students competence holistic achievment  such us in knowledge, attitude, and also skill. it was proven by looking into 2013 curriculum which improved the balance in student’s hardskill and softskill. But, in the fact, analysis result of curriculum 2013 learning such as learning processes, learning device, and evaluation studying have not been achieved properly. The solution to these problem was the use of teaching material which integrated with spiritual intelligence in problem based model for competence achievement of grade X SMAN 16 padang students. This research used quasi experiment research which randomized control group only design. The research population sampling is grade X MIA 4 as experiment class and X MIA 5 as control class. The obtained data included spiritual attitude competence, knowledge, and skill of students. Data analysis for all data were processed by descriptive statistic, two average equations test, simple linier regresion and corelation analysis. Based on data analysis, conlude that there were significant different and impact for students achievement by using teaching material which integrated with spiritual intellegence for grade X SMAN 16 Padang, which significant value 0,05.